Analisis Kontribusi Pertumbuhan Sektor Pertanian terhadap PDRB dan Struktur Pertumbuhan Ekonomi Kabupaten/Kota di Provinsi Riau Indonesia Tahun 2017-2023 - Nindya Pangestu; Sisca Vaulina (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2025)
Riau Province, situated in Sumatra, plays a significant role in Indonesia’s national Gross Domestic Product (GDP). However, it continues to experience notable economic disparities among its regencies and cities. The purpose of this study is to examine: (1) the economic growth in Riau Province from 2017 to 2023, (2) the contribution of the agricultural sector to the provincial GDP, and (3) the structure of regional economic growth. A quantitative approach was applied using secondary data from a seven-year time series (2017–2023). The analytical methods used include economic growth analysis, Location Quotient (LQ), and Klassen Typology. The results show that Dumai City achieved the highest average economic growth rate, while Bengkalis Regency experienced the lowest. Eight regencies were identified as having agriculture as a basic sector (LQ > 1), while four regions were classified as non-basic (LQ < 1). Klassen Typology results show that most areas fall under the “growing but not yet developed” category. These findings highlight significant spatial disparities in economic structure and performance, underlining the importance of region-specific development policies. Strengthening agriculture-based regions and diversifying non-agricultural economies are essential steps toward achieving more balanced economic growth in Riau Province.